(untitled) (Global Journal of Human-Social Science, 2025)
The article examines the thesis of the productivity of the unproductive school in the Brazilian context drawing on IDEB Adequate Learning in Portuguese Language and Mathematics across the three stages of basic education early and final years of elementary education and upper secondary education Methodologically it is a documentary-analytical study with a quantitative and critical approach based on secondary analysis of public indicators The empirical strategy combines descriptive statistics trend analysis and relative differences between stages and school networks with a methodological choice to track Adequate Learning rather than aggregate indices and to disaggregate by subject area and stage in order to mitigate interpretive distortions The results indicate insufficient national levels and a sharp decline from elementary to upper secondary more intense in Mathematics e g 2023 44 16 5 and also present in Portuguese Language 55 36 32 a pattern observed in the private school network and attenuated though not overcome in the federal network The article argues that instructionism lesson test transmission sustains a system that fails to ensure learning producing what we term an unlearning effect a cumulative phenomenon it also discusses the limitations of IDEB-Proficiency justifying the focus on Adequate Learning by subject and stage On the prescriptive side it advocates shifting policies and practices toward public research cycles with student authorship iterative versions and explicit rubrics under the principle of the same yardstick multiple pathways procedural equity It concludes that the diagnosis is not intended to blame teachers but to inform decisions that reconfigure the school as a learning architecture grounded in evidence and the public dissemination of results